The effectiveness of the digital game Kahoot on vocabulary acquisition - Talapova A.K.; Abdusalamova A.M. (World Scientific Reports, 2024)
This study examines the effectiveness of the digital game Kahoot! in improving vocabulary acquisition among 3rd and 4th-year university students. Using a quantitative design, data were collected through a questionnaire on vocabulary recall, motivation, ease of use, and comparison to traditional methods. The findings show that Kahoot! significantly boosts vocabulary recall, motivation, and engagement. Despite its benefits, challenges such as technology access and teacher training are noted. The study concludes that Kahoot! is an effective tool for enhancing vocabulary learning.